Transcranial Direct Current Stimulation May Reduce Prefrontal Recruitment During Dual Task Walking in Functionally Limited Older Adults – A Pilot Study - Jor’dan, Azizah J.; Bernad-Elazari, Hagar; Mirelman, Anat; Gouskova, Natalia A.; Lo, On-Yee; Hausdorff, Jeffrey M.; Manor, Brad (Frontiers in Aging Neuroscience, 2022)
ABSTRACT Introduction: Transcranial direct current stimulation (tDCS) targeting the left dorsolateral prefrontal cortex (dlPFC) improves dual task walking in older adults, when tested just after stimulation. The acute effects of tDCS on the cortical physiology of walking, however, remains unknown. Methods: In a previous study, older adults with slow gait and executive dysfunction completed a dual task walking assessment before and after 20 minutes of tDCS targeting the left dlPFC or sham stimulation. In a subset of seven participants/group, functional near-infrared spectroscopy (fNIRS) was used to quantify left and right prefrontal recruitment defined as the oxygenated hemoglobin response to usual and dual task walking (ΔHbO2), as well as the absolute change in this metric from usual to dual task conditions (i.e., ΔHbO2cost). Paired t-tests examined pre-to-post-stimulation differences in each fNIRS metric within each group. Results: The tDCS group exhibited pre-to-post stimulation reduction in left prefrontal ΔHbO2cost (p=0.03). This mitigation of dual task ‘cost’ to prefrontal recruitment was induced primarily by a reduction in left prefrontal ΔHbO2 specifically within the dual task condition (p=0.001), an effect that was observed in all seven participants within this group. Sham stimulation did not influence ΔHbO2cost or ΔHbO2 in either walking condition (p>0.35), and neither tDCS nor sham substantially influenced right prefrontal recruitment (p>0.16). Discussion: This preliminary fNIRS data suggests that tDCS over the left dlPFC may modulate prefrontal recruitment, as reflected by a relative reduction in the oxygen consumption of this brain region in response to dual task walking.